COLLABORATIVE-COOPERATIVE LEARNING MODEL TO IMPROVE THEOLOGY STUDENTS’ CHARACTERS: IS IT EFECTIVE? - GP Harianto; Rusijiono Rusijiono; Siti Masitoh; WH Setyawan (Jurnal Cakrawala Pendidikan, 2020)
The Collaborative-Cooperative Learning Model (CCL) helps improve students’ characters. This study is aimed at finding out the effectiveness of the CCL instructional model in improving the characters of the theology students in the subject matter class Self Development. The study used the quasi-experimental research design. The research sample consisted of 58 students of the Surabaya Excelsius Institute of Theology. Data were collected by way of a test in a pre-test and posttest for the experiment and control groups and analyzed by way of an independent sample t-test on the SPSS software program of Amos 25. Results show that (1) the CCL model is found to be able to improve students’ characters. Experts’ reviews conclude that the CCL syntax can be categorized as having innovative aspects based on the rationality model on the score of 3.29; (2) The CCL model is found to be effective in improving students’ characters by the Mann-Whitney test (sig. = 0,012) and the paired sample t-tes (sig. = 0.000) showing a significant difference in the mean scores; (3) the CCL model can improve the characters of self-discipline, social discipline, and religious discipline  in the theology students in the subject matter class Self Development and can be used for subject matter classes with the same characteristics, be followed-up by research in wider subject-matter contexts, and be integrated  with research from other academic fields.